Role of Psychological Distress in the Assessment of Chronic Illness Care and Self-Management Behaviors of Elderly Patients with T2DM Chronic Complications - Sun X; Wang X; Zhou R; Deng W; Jiang J; Shi Y (Diabetes, Metabolic Syndrome and Obesity)
Xiao Sun,1 Xue Wang,2 Rongrong Zhou,3 Wei Deng,4 Jinxia Jiang,2 Yan Shi5 1Department of Nursing, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of China; 2Department of Emergency, Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of China; 3School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of China; 4Department of Colorectal Disease, Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of China; 5Department of Nursing, Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of ChinaCorrespondence: Jinxia Jiang; Yan Shi, Email jiangjinxia99@163.com; 2080153@tongji.edu.cnBackground: This study sought to explore the interrelationship between diabetes-related distress, patient evaluations of chronic illness management, and self-management practices among older adults diagnosed with T2DM and associated chronic complications.Methods: This was a cross-sectional study including 264 older adults with T2DM in Shanghai, China. Chinese version of Problem Areas in Diabetes Scale (PAID-C), Patient Assessment of Chronic Illness Care (PACIC) and Diabetes Self-Management Behaviour for Older (DSMB-O) were employed. Student’s t-test, one-way ANOVA or the nonparametric analysis (Mann–Whitney U-test), Pearson correlation coefficient and structural equation model (SEM) were used to analyse the data.Results: A total of 264 participants (157 males [59.47%], with an average age of 71.07± 6.47 years) were included in the study; their duration of T2DM ranged from 5 to 30 years, with a mean duration of 11.19± 6.96 years. The DSMB-O scores exhibited a negative correlation with the PAID-C scores (r=− 0.250, p< 0.01), while showing a positive correlation with PACIC scores (r=0.348, p< 0.01). Additionally, PAID-C scores demonstrated a negative correlation with PACIC scores (r=− 0.182, p< 0.01). The indirect effect of PAID-C on DSMB-O through PACIC was calculated as (− 0.70*-0.39=0.27). Furthermore, the total effect of PAID-C on DSMB-O via PACIC was determined to be (0.27+0.22=0.49). Notably, the mediating effect accounted for 54.99%.Conclusion: Psychological distress is intricately linked to self-management behaviour among elderly patients suffering from T2DM and chronic complications. Our findings carry significant implications for T2DM healthcare, indicating that addressing psychological distress may enhance the quality of chronic illnesses, ultimately fostering improved self-management practices and yielding better health outcomes.Keywords: psychological distress, chronic illness care, self-management behaviors, elderly, type 2 diabetes mellitus